محددات الموقف الروسي من الأزمة السورية - صيوح لؤي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدف البحث إلى التعرف على محددات الموقف الروسي من الأزمة السورية الراهنة، وذلك من خلال تحديد طبيعة المصالح الروسية والرؤية المستقبلية للسياسة الخارجية الروسية تجاه الأزمة السورية . اعتمد البحث على تكامل منهجي بين منهجين: المنهج التاريخي المقارن والمنهج الوصفي التحليلي وذلك من أجل إظهار الإطار الحالي للعلاقات الروسية والإطلاع على مواطن التغير فيها . ومن أهم النتائج التي توصل إليها البحث : 1- مايحدث على الساحة السورية هو انعكاس لما يجري على المستوى الإقليمي والدولي من تنافس وصراع بين القوى الكبرى في الشرق الأوسط. 2- تنظر روسيا إلى الأزمة السورية كتهديد لمصالحها الإستراتيجية في الشرق الأوسط. 3- اتسمت المواقف الروسية من الأزمة السورية بالاعتدال والتوازن. وفي ضوء نتائج البحث، فقد أوصى الباحث بضرورة استمرار العلاقات بين روسيا وسورية والتوجه إلى تكثيفها في المرحلة المقبلة. The research aims to identify the determinants of the Russian position on the current crisis in Syria, and that is by identifying the nature of Russian interests, and the future vision of the Russian foreign policy towards the Syrian crisis. The research depended on the systematic integration between the two approaches: the historical comparative approach and the analytical descriptive approach. And that is to show the current frame of the Syrian-Russian relations and to get to know the changes in it. The most important results of the research are: 1. what is happening on the Syrian arena is a reflection of what is happening on the regional and international level in terms of competition and conflict between the major powers in the Middle East. 2. Russia sees the Syrian crisis as a threat for her strategic interests in the Middle East. 3. Russian positions on the Syrian crisis were moderate and balanced. In light of these results, the researcher recommends to continuing of relations between Russia and Syria and proceeding to reinforce them in the next phase.